Effectiveness of Nanoparticles in Enhancing Bond Strength in Adhesive Dentistry - Ullash Kumar; Dewanshu Kumar; Khyati N Gosai; Dhanashree Dalal; B Pragnya; Sayeeganesh Nagarajan (Journal of Pharmacy and Bioallied Sciences)
Background: New opportunities for improving material qualities and clinical results have been created by the introduction of nanotechnology in dentistry. The ability of nanoparticles to strengthen the binding between adhesives used in restorative dentistry has drawn more attention. This is because successful and long-lasting dental procedures depend on strong adhesives. The purpose of this research is to determine if silica and zirconia nanoparticles may improve the bond strength of dental adhesives. Materials and Methods: The adhesive treatments applied to 60 removed human molars were separated into three groups at random: ordinary adhesive, adhesive combined with silica nanoparticles, and adhesive combined with zirconia nanoparticles. For both experimental groups, the nanoparticle concentration was normalized to 5% by weight. After being stored in distilled water at room temperature for 24 hours, the bond strength was assessed using a universal testing equipment. Results: There were notable variations across the groups based on the bond strength tests. The silica nanoparticle group had an improved binding strength of 30 MPa, compared to an average bond strength of 22 MPa for the traditional adhesive group. At an average of 35 MPa, the zirconia nanoparticle group showed the strongest bond. A statistical study verified that there were significant differences (P < 0.05) between each of the adhesives boosted with nanoparticles and the regular glue. Conclusion: Dental adhesives using silica and zirconia nanoparticles considerably improve binding strength over traditional adhesives. The exceptional binding strength of zirconia nanoparticles, in particular, raises the possibility of their practical use in adhesive dentistry to lengthen the lifespan of dental restorations.